Pendidikan Ekoteologi dalam Perjumpaan Antara Falsafah Tallu Lolona Orang Toraja dan Nilai-Nilai Kristiani - Upa', Febriani (Jurnal Shanan, 2023)
Ecological issues are one of the struggles that people around the world are experiencing. Ecological problems that continue to occur are also one of the struggles of the people of Toraja, South Sulawesi. This study aims to explore the local wisdom of the Toraja people through the Tallu Lolona philosophy in encounters with Christianity. This research utilizes literature studies on a number of literature related to ecological issues both from the perspective of Toraja culture and Christian religious values. The results of the study show that the encounter between tallu lolona's philosophy and Christian faith can become a reciprocal critical dialogue in efforts to prevent as well as overcome the ecological crisis that occurred in Toraja. The encounter between the two shows that each contributes to efforts to create peace and the integrity of creation.